Joint Simulation of a Marine High Power Hydraulic Control Clutch Transmission System - Wang Xuezhi; Yan Ze; Feng Liju; Chen Kexin; Wang Yongfan; Zhan Qingxin; Li Chao; Qu Dongyue (Jixie chuandong)
In this study, the joint simulation flow of Adams and AMESim on the kinematics and contact dynamics of the marine high-power hydraulic drive gear clutch is studied, and the joint simulation interactive operation interface is developed. With the given parameters, the visual calculation results can be output. The simulation results show that the dynamic characteristics and impact load of the gear clutch during the axial engagement are affected by the torsional stiffness of the active end and the end face structure of the gear. The maximum opening pressure of the pressure reducing valve is 2.5 MPa, and the maximum thrust under this pressure is 1.884×105 N. When the inner and outer rings collide, the oil pressure will rise rapidly. If the flow of the pressure reducing valve is insufficient, the oil inlet will leak. After multiple joint simulations, it is found that the clutch engagement and disengagement process can be completed around 4 s when the inlet pressure is between 0.008 MPa and 0.01 MPa.